Multivariate statistical evaluation of dissolved trace elements and water quality assessment in the Karaca dam, Turkey - Banu Kutlu; Ekrem Mutlu (EQA - International Journal of Environmental Quality, 2021)
This study was performed from January 2017 to December 2017 with taking samples every month from four stations to determine the water quality of Karaca Dam, located in Sinop. The guidelines of the World Health Organization for water quality index (WQI) and Turkey’s Ministry of Forestry and Water Affairs specifications for Surface Water Quality Regulations (SWQR) were used in the determination of water quality and 28 variables were analyzed. The quality of the irrigation water was also calculated. This objective, the sodium adsorption ratio (SAR), sodium percentage, permeability index (PI), and magnesium index were calculated. The average WQI value of the lake was found to be 19.23. It was observed that the water quality parameters did not exceed the restrictions in any stations during the period. According to the results of the research, Karaca Dam is in a good class in terms of drinking water quality and irrigation water. The health risk evaluation, using the hazard ratio and index (HI), was carried out as suggested by USEPA, and it was found that the water of Karaca Dam is not harmful to human health in terms of Pb, Cd, and Hg.

EQA - International Journal of Environmental Quality, Vol. 44 (2021)
Keywords: irrigation water quality; TD172-193.5; water quality index; surface water; water quality; Environmental pollution; 13. Climate action; 14. Life underwater; 6. Clean water; 3. Good health